Scenario approach to agricultural development in Azerbaijan - Hajiyeva, Nadjiba Gabilqizi (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The purpose of this paper is to substantiate the optimal scenario to develop agriculture for the effective diversification of the Azerbaijani economy. By constructing an intersectoral balance model and using regression analysis, we propose the approach for determining optimal agriculture development scenarios taking into account the current development trends of the industry: innovative, inertial, and balanced. Using the balance model helps to account for the cause-and-effect relationships between the indicators of the development of all sectors of the Azerbaijani economy and comprehensively assess the impact of agricultural development on the diversification of the national economy. In contrast to the classical balance model, the modified model proposed in our article provides possibilities to assess not just the production potential of industries but also their contribution to the formation of the country’s GDP and diversification of the economy on the way to neutralizing oil dependence.